The effects of tourism e-commerce live streaming features on consumer purchase intention: The mediating roles of flow experience and trust - Liu, Xiaoli; Zhang, Lei; Chen, Qian (Frontiers in psychology, 2022)
Given that tourism e-commerce live streaming has become an important driver of tourism development after the outbreak of Covid-19 but limited attention has been paid to this area, this study examines the impacts of tourism e-commerce live streaming features (interactivity, authenticity, and entertainment) on the consumers’ purchase intention from the perspectives of consumers’ flow experience and trust based on the SOR theory. The authors collected survey data from 357 tourism e-commerce live streaming consumers and used the structural equation model to test the research model. The results reveal that interactivity and authenticity positively affect tourism e-commerce live streaming consumers’ purchase intention, but entertainment does not influence purchase intention positively; interactivity, authenticity, and entertainment each positively affects tourism e-commerce live streaming consumers’ flow experience and trust; both flow experience and trust positively affect tourism e-commerce live streaming consumers’ purchase intention; both flow experience and trust have mediating effects on the relationships between tourism e-commerce live streaming features and consumers’ purchase intention. This study extends existing theoretical research on tourism e-commerce live streaming and provides some managerial implications for tourism enterprises and streamers.